Design of a Tunable Metamaterial Absorption Device with an Absorption Band Covering the Mid-Infrared Atmospheric Window - Zongliang He; Dong Fang; Yougen Yi (Photonics)
We propose a highly efficient broadband tunable metamaterial infrared absorption device. The design is modeled using the three-dimensional finite element method for the absorption device. The results show that the absorption device captures over 90% of the light in the wavelength range from 6.10 μm to 17.42 μm. We utilize VO2’s phase change property to adjust the absorption device, allowing the average absorption level to vary between 20.61% and 94.88%. In this study, we analyze the electromagnetic field distribution of the absorption device at its peak absorption point and find that the high absorption is achieved through both surface plasmon resonance and Fabry–Perot cavity resonance. The structural parameters of the absorption device are fine-tuned through parameter scanning. By comparing our work with previous studies, we demonstrate the superior performance of our design. Additionally, we investigate the polarization angle and incident angle of the absorption device and show that it is highly insensitive to these factors. Importantly, the simple structure of our absorption device broadens its potential uses in photodetection, electromagnetic stealth, and sensing.